1996
DOI: 10.1088/0953-4075/29/9/018
|View full text |Cite
|
Sign up to set email alerts
|

A classical analysis of proton collisions with ground-state and excited, aligned sodium targets

Abstract: The dependence of electron capture and ionization processes on the pre-collision electronic distribution is examined for the systems primarily in the energy range 1 - 15 keV. Populations of the capture and ionization channels as well as the coherence of the post-collision electronic distribution of the capture product are formulated using the classical trajectory Monte Carlo (CTMC) method. Total capture and ionization cross sections arising from initially aligned Na(3p) targets exhibit transient behaviour nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Later a generalized scaling law Figure 3. Absolute single ionization cross sections for different projectiles colliding on both Na(3s) and Na * (3p), including TC-BGM calculations for H + +Na(3s) [13] (--) and CTMC calculations for H + +Na * (3p) [22] (----) and He 2+ +Na(3s) [14] [10,11], also showing their result of a fit of H and He data.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Later a generalized scaling law Figure 3. Absolute single ionization cross sections for different projectiles colliding on both Na(3s) and Na * (3p), including TC-BGM calculations for H + +Na(3s) [13] (--) and CTMC calculations for H + +Na * (3p) [22] (----) and He 2+ +Na(3s) [14] [10,11], also showing their result of a fit of H and He data.…”
Section: Resultsmentioning
confidence: 81%
“…The absolute cross sections for single ionization of Na * (3p) were obtained using the cross sections for capture from Na(3s) and applying the cross section ratio between Na(3s) and Na * (3p). Theoretical cross sections are available from TC-BGM (H + +Na(3s) [13]) and classical trajectory Monte Carlo (CTMC) calculations (H + +Na * (3p) [22], He 2+ +Na(3s) [14]). Note that for the H + +Na(3s) system CTMC calculations [22] yield about 20-25% smaller cross sections compared to the TC-BGM calculations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At these projectile energies it is now well established that an expansion of the wavefunction in either atomic (AO) or molecular (MO) basis states is adequate and, in general, gives an excellent agreement with experiments for total and partial cross sections [4] and phase-dependent coherence parameters [3,5]. Recently, it has also been demonstrated that the classical trajectory Monte Carlo (CTMC) method gives the correct relative distribution for the H(n = 2) channels in capture from laser-excited Na(3p −1 ) [6][7][8][9]. At higher energies much less is known about the state-to-state dynamics in collisions between charged particles and laser-excited atoms.…”
Section: Introductionmentioning
confidence: 86%
“…Thus total and state-to-state asymmetries in differential scattering may now be studied and compared to theory at the most fundamental level of one-electron quantum dynamics. Since the classical trajectory Monte Carlo (CTMC) method has been used with various degrees of success for many such related studies also involving ionization [3][4][5][6][7], one may ask whether there are any distinct quantum signatures at all involved in the collision dynamics. Our previous studies of collisions between singly charged ions and excited atoms have displayed, however, some clear discrepancies for electron capture.…”
mentioning
confidence: 99%